Analisis Perbedaan Proses dan Hasil Pendidikan Pesantren Salafiyah dan Perguruan Tinggi Keagamaan Islam (PTKI) Untuk Merumuskan Model Pendidikan Islam Transformatif - Anis Humaidi; Najihatul Fadhliyah (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
One of the aims of establishing Islamic boarding schools and religious colleges (PTKI) is to produce a cadre of ulama' (experts in Islamic science). These two institutions have their own ways and processes in realizing their goals. Because of the differences in methods and processes, the results are also different. This article reveals the process of education at Salafiyah Islamic boarding schools and education at Islamic religious colleges. This article also reveals the results of Islamic boarding schools and education from Islamic religious universities. This research approach is qualitative, interviews and observation are the main instruments for data collection. The results of this research are that, in the educational process at Islamic boarding schools, almost all of the teaching materials come from the classical book. The methods are bandongan, sorogan and deliberation. The results of education from Salafiyah Islamic boarding schools are that graduates have more mastery of religious texts but lack contextual courage. Meanwhile, in the PTKI religious higher education process, the teaching materials come from various sources, both classical books and modern literature, the learning method mostly uses the discussion method. PTKI Education Results More contextual courage but most do not master religious texts in depth. Each of the two institutions, both Islamic boarding schools and PTKI, has weaknesses and strengths.